Editorial Revista Digital do LAV – vol.8, n.3, set./dez. 2015. - Oliveira, Marilda Oliveira de; Charréu, Leonardo (Revista Digital do LAV, 2015)
Editorial Revista Digital do LAV – Laboratório de Artes Visuais – vol.8, n.3, set./dez. 2015. ISSN: 1983-7348